DIALEKTIKA TRADISI DAN MODERNITAS: STUDI FENOMENOLOGI WEDANGAN MASA KINI DI SURAKARTA - Muhammad Ikhwal Sukirman; Imri Yonaldi Tefa; Salwa fadilla Khailifa; Reza Zain Ananta Sukirman (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
This study aims to analyse the dialectic between tradition and modernity in the transformation of wedangan in the city of Surakarta. Historically, wedangan served as an egalitarian culinary space and a source of social cohesion based on subsistence strategies. However, in the contemporary urban context, wedangan has undergone a reconstruction of meaning with the emergence of modern wedangan. This study explores the cultural strategies employed by wedangan owners in reinterpreting tradition, as well as understanding visitors’ perceptions of today’s wedangan. This study employs Alfred Schutz’s phenomenological qualitative approach, supported by netnographic data and field observations conducted at three wedangan locations in Surakarta, namely Wedangan Pendhopo, Wedangan Sakeca and Wedangan Oemah Joglo as well as in-depth interviews. The results of this study indicate that contemporary wedangan are hybrid entities that reconstruct Javanese cultural symbols as an adaptation strategy within the framework of multiple modernities, whilst simultaneously serving as an arena for class distinction through the commodification of nostalgia. This transformation has led to the fading of the wedangan’s function as an egalitarian public space and the strengthening of individualistic consumption patterns among the urban middle class. These findings contribute to a sociological understanding of the negotiation of local culinary traditions within the currents of urban modernity.